Study about the launching of the game from the margins statics phase in rugby for U15-U16 junior groups - Popescu, R.; Mocanu, N. R.; Tranca, S.-C. (Science, Movement & Health, 2020)
Argument. The margin fixed moment has a special importance as the launches in the game present a large range of attack options but also the possibility to test the vigilance of the defense team. This fixed phase, besides the multitude of attack possibilities with participants on the margins, may also generate a full speed attack of the backs as the regulation specifies that the players who are not involved in the game should be placed at least 10 meters away, space which allows the payers to lead the ball in any attack area. We may say that the launching of the game can have an important role in winning the game but can also grant the rugby game a spectacular touch. It is very important to pay a special attention to this fixed moment of the rugby game starting with the youngest groups of children and juniors in order to create a solid base for the senior teams and for the national team of Romania. Methods. I have chosen as case study methods, the observation and the speaking method. I have monitored the evolution of the under 15 team from "Nicolae Rotaru" Sports High School of Constanta which played in the Junior National League during the whole competitive year, both during groups phase as well as in the finals, before and after (round-trip matches) 2018. The accent on the specific training was done between the round-trip matches especially, during the specific training in the mountains, Tusnad place. In the period between the round-trip matches, the training period included, I have followed the improvement of the margin game and I have awarded a special attention to specific training. I have insisted on reaction speed improvement and the development of the force for speed operation. To develop the force for speed operation I used intensities between 65%-95%, with 4-6 repetitions and 5-6 series in a cycle of 4-6 exercises. These exercises were performed in a space of 10 meters while trying to approach the margin fix moment positioning. Furthermore, for an increased efficiency, the exercises have been performed on a downhill and the snow helped us to raise the efficiency of the selected games and exercises. Conclusion. After the training program, the margin efficiency increased with 13,1 %, as follows: the team benefited of more balls and more launches. The percentage was of 76,6 in the first games versus 64,5. This also led to the raise of possession. We had a 66,2 % possession in the second match versus 57,3 % in the first half of the championship, so there was a raise of 8,9%. Thus, it can be noticed the improvement between the two halves of the championship, which it was also confirmed as we won the championship at the end of the competitive year. Beyond possession, the balls won and the "won ground" thanks to this technique raised from 13,6 to 20,4 balls won each match.